Gunilla Tegengren: Sverige och Nordlanden. Förvaltning och nordlig expansion 1250-1550 - Stefan Figenschow (Novus, 2017)
For any scholar studying the expansion of Scandinavian central authority into what is often regarded as peripheral areas of medieval Fennoscandia, the publication of Gunilla Tegengren's doctoral dissertation Sverige och Nordlanden. Förvaltning och nordlig expansion 1250-1550 is a welcome addition. The book should be of interest to anyone with a predilection for Swedish medieval history in general, a desire to explore the process of integrating the northern part of present day Sweden in the medieval Swedish kingdom, or those focusing on similar processes elsewhere in Northern Europe. Whilst the Swedish medieval expansion to the southern parts of present day Finland, including the clashes with the Russian city-state of Novgorod that relate to this process, is quite well covered, works on the scale of Sverige och Nordlanden regarding the northward expansion of Swedish central authority are not as manifold.